Children's views on research without prior consent in emergency situations: a UK qualitative study. Issue 6 (9th June 2018) - Roper, Louise; Sherratt, Frances C; Young, Bridget; McNamara, Paul; Dawson, Angus; Appleton, Richard; Crawley, Esther; Frith, Lucy; Gamble, Carrol; Woolfall, Kerry
Abstract : Objectives: We explored children's views on research without prior consent (RWPC) and sought to identify ways of involving children in research discussions. Design: Qualitative interview study. Setting: Participants were recruited through a UK children's hospital and online advertising. Participants: 16 children aged 7–15 years with a diagnosis of asthma (n=14) or anaphylaxis (n=2) with recent (<12 months) experience of emergency care. Results: Children were keen to be included in medical research and viewed RWPC as acceptable in emergency situations if trial interventions were judged safe. Children trusted that doctors would know about their trial participation and act in their best interests. All felt that children should be informed about the research following their recovery and involved in discussions with a clinician or their parent(s) about the use of data already collected as well as continued participation in the trial (if applicable). Participants suggested methods to inform children about their trial participation including an animation. Conclusions: Children supported, and were keen to be involved in, clinical trials in emergency situations. We present guidance and an animation that practitioners and parents might use to involve children in trial discussions following their recovery.